A deadly feast: Elucidating the burden of orally acquired acute Chagas disease in Latin America – Public health and travel medicine importance. Issue 36 (July 2020) - Franco-Paredes, Carlos; Villamil-Gómez, Wilmer E.; Schultz, Jonathan; Henao-Martínez, Andrés F.; Parra-Henao, Gabriel; Rassi, Anis; Rodríguez-Morales, Alfonso J.; Suarez, José Antonio
Abstract: Over the past two decades, several countries in Latin American, particularly Brazil, Venezuela, and Colombia, have experienced multiple outbreaks of oral Chagas disease. Transmission occurs secondary to contamination of food or beverages by triatomine (kissing bug) feces containing infective Trypanosoma cruzi metacyclic trypomastigotes. Orally transmitted infections are acute and potentially fatal. Oral Chagas transmission carries important clinical implications from management to public health policies compared to vector-borne transmission. This review aims to discuss the contemporary situation of orally acquired Chagas disease, and its eco-epidemiology, pathogenesis, and clinical management. We also propose preventive public health interventions to reduce the burden of disease and provide important perspectives for travel medicine. Travel health advisors need to counsel intending travellers to South America on avoidance of "deadly feasts" - risky beverages such as fruit juices including guava juice, bacaba, babaçu and palm wine ( vino de palma ), açai pulp, sugar cane juice and foodstuffs such as wild animal meats that may be contaminated with T. cruzi .